(untitled) (Journal of Contemporary Issues in Accounting, 2023)
This study examined the effect of financial deepening on economic growth in Nigerian from 1986 to 2020 using data sourced from the CBN statistical bulletin (2020). The Nigerian financial sector is beleaguered with fissures that have frustrated its potential to facilitate economic growth, Funds accumulated by financial intermediaries are insufficient to cater for the desired level of economic growth. The objective of this study was to find out how financial deepening has influenced the economy. Financial deepening was measured by money supply to GDP, insurance premiums to GDP, Stock market capitalization to GDP and private sector credit to GDP while economic growth was represented by real GDP. The study adopted the ex-post facto research design in conducting the research. The data was subjected to statistical analysis using the Ordinary Least Square regression. The findings of the study revealed that money supply to GDP and Market capitalization to GDP has positive and significant relationship with economic growth in Nigeria while private sector credit to GDP and insurance premiums to GDP ratio had negative relationship with economic growth in Nigeria. The study recommends that Credit to private sectors should be channeled to the real sector of the economy which will lead to economic growth. The monetary authorities should also ensure adequate supply of money to facilitate economic transactions for economic growth to desired levels. The monetary authorities should develop policies that aids entry of more establishments into the capital market and Insurance policies should be made to ensure the relevance and increased patronage of insurance sector in Nigeria.